Palm oil moisture monitoring based on dielectric properties at microwave frequencies - You, Kok Yeow; Abbas, Zulkifly; You, Li Ling; Lee, Kim Yee; Cheng, Ee Meng (International Journal of Microwave and Optical Technology, 2014)
This paper focuses on the determination of the degree of the emulsion for the water-in-palm oil mixture. The degree of emulsion of the mixture is dependent on the properties of dielectric constant. The dielectric properties of the mixtures were measured using Agilent dielectric probe with frequencies ranging from 1 GHz to 18 GHz. Two types of mixture rules were discussed and respectively used in the modeling of the dielectric properties of both crude palm oil and crude kernel palm oil. The macroscopic analysis on the mechanisms occurs in both water-palm oil mixtures were carried out and discussed in detail.